Modeling of Gate Tunable Synaptic Device for Neuromorphic Applications - Shen, Yang; Tian, He; Liu, Yanming; Wu, Fan; Yan, Zhaoyi; Hirtz, Thomas; Wang, Xuefeng; Ren, Tian-Ling (Frontiers in Physics, 2021)
The emerging memories are great candidates to establish neuromorphic computing challenging non-Von Neumann architecture. Emerging non-volatile resistive random-access memory (RRAM) attracted abundant attention recently for its low power consumption and high storage density. Up to now, research regarding the tunability of the On/Off ratio and the switching window of RRAM devices remains scarce. In this work, the underlying mechanisms related to gate tunable RRAMs are investigated. The principle of such a device consists of controlling the filament evolution in the resistive layer using graphene and an electric field. A physics-based stochastic simulation was employed to reveal the mechanisms that link the filament size and the growth speed to the back-gate bias. The simulations demonstrate the influence of the negative gate voltage on the device current which in turn leads to better characteristics for neuromorphic computing applications. Moreover, a high accuracy (94.7%) neural network for handwritten character digit classification has been realized using the 1-transistor 1-memristor (1T1R) crossbar cell structure and our stochastic simulation method, which demonstrate the optimization of gate tunable synaptic device.